Potent nonopioid antinociceptive activity of telocinobufagin in models of acute pain in mice - Geissy I.M.C. Feitosa; Isabella F. Carvalho; Edivaldo B.S. Coelho; Marla R.B. Monteiro; Rafael L. Medeiros; Ellaine D.F. Carvalho; Paulo T. A. Silva; Dóris M.F. Carvalho; Daniel E.A. Uchoa; Edilberto R. Silveira; Cláudia F. Santos; Nilberto R. Nascimento; et al. (PAIN Reports, 2019)
Abstract. Introduction:. In recent decades, several researches have been conducted in search of new analgesics that do not present the side effects of opioids. In this context, animal venoms contain natural painkillers that have been used for the development of new analgesics. Objective:. The aims of this study were to evaluate the antinociceptive effects of telocinobufagin (TCB), a bufadienolide isolated from Rhinella jimi venom, in murine acute pain models, and to verify the participation of the opioid system in these effects. Methods:. TCB was purified from R. jimi venom by high-performance liquid chromatography, and its structure was confirmed by spectrometric techniques. TCB was administered intraperitoneally (i.p.) (0.062, 0.125, 0.25, 0.5, and 1 mg·kg−1) and orally (p.o.) (0.625, 1.125, 2.5, 5, and 10 mg·kg−1) in mice, which were then subjected to pain tests: acetic acid–induced writhing, formalin, tail-flick, and hot-plate. Involvement of the opioid system in TCB action was evaluated by naloxone i.p. injected (2.5 mg·kg−1) 20 minutes before TCB administration. In addition, the TCB action on the μ, δ, and κ opioid receptors was performed by radioligand binding assays. Results:. In all the tests used, TCB showed dose-dependent antinociceptive activity with more than 90% inhibition of the nociceptive responses at the doses of 1 mg·kg−1 (i.p.) and 10 mg·kg−1 (p.o.). Naloxone did not alter the effect of TCB. In addition, TCB did not act on the μ, δ, and κ opioid receptors. Conclusion:. The results suggest that TCB may represent a novel potential nonopioid therapeutic analgesic for treatment of acute pains.